Management and Outcome of Chylous Ascites in Children: A CARE compliant Case Series - Magd A. Kotb; Dalia S. Mosallam; Heba Amin Ragab; Hend Abd El Baky; Ahmed El Hatw; Alaa F. Hamza; Hesham Abd El Kader; Gamal El Tagy; Haytham Esmat; Sherif Shehata; Nahla I. Sabry (Cairo University, Faculty of Medicine, Department of Pediatrics, 2021)
Background: Chylous ascites (CA) is accumulation of lipid rich lymph in peritoneal cavity. CA is rare among children. In pediatric age, causes of CA varies according to the age group, leading primary causes include congenital malformation of lymphatic system, and less likely lymphatic obstruction such as intestinal malrotation, gastroschisis, infections or trauma of thoracic duct. Aim of the work: We aim to report outcome of congenital CA in a pediatric cohort. Material and Methods: Retrospective analysis of data of 4 children (4 boys) who presented by CA to New Children Hospital, Cairo University during 2010- 2018. Results: Duration of follow up of the boys was 6.5, 5, 2.5, and 0.25 years respectively. All presented by abdominal distention and diagnostic tapping of ascitic fluid revealed triglyceride level more than 200 mg%, protein more than 2 g% and/or a cell count greater than 500 /cmm with a predominance of lymphocytes (> 80%). Lymphatic scintigraphy in 3 of them revealed no abnormality in lymph drainage. The course of disease was punctuated by chylothorax, and chylous hydrocoele in all 4 cases. All 4 did not respond to medium chain triglyceride based diet. One child underwent peritenovenous shunt, and the other 3 responded to somatostatin analogue octreotide SC injections during hospital stay and maintenance therapy. Last child was lost to follow up. All other 3 are fine with minimal complications and living with mild peritoneal ascites. Conclusion: Somatostatin analogue therapy provided well-tolerated non-invasive control of congenital CA in our studied pediatric cohort. Surgical intervention should be restricted to those with underlying surgical cause and in those failing to respond to medical treatment.